2021
DOI: 10.3390/ijerph182413245
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training for Multiple Sclerosis: A Narrative Review of History, Benefits, Safety, Guidelines, and Promotion

Abstract: Background: There have been significant advances in the medical treatment and management of multiple sclerosis pathogenesis, relapse and disease progression over the past 30 years. There have been advancements in the symptomatic treatment of multiple sclerosis, including management of secondary multiple sclerosis expressions such as walking, cognitive dysfunction, fatigue and depression. Scientific evidence and expert opinion suggest that exercise may be the single most effective non-pharmacological symptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 75 publications
0
13
0
1
Order By: Relevance
“…Physiotherapy and rehabilitation NICE guidelines on symptom management in MS highlight the importance of offering people with MS and mobility problems access to rehabilitation specialists and physiotherapists with expertise in MS. 11 Evidence and expert opinion have suggested that the combination of mechanical, manual and educational interventions in physiotherapy programmes which are tailored to the individual's needs may be the single most effective non-pharmacological symptomatic treatment for MS. 12 Apart from mobility, physiotherapy has also been found to be beneficial in treating cognitive and mood disturbances, pareses, spasticity and fatigue. 13 At least one physiotherapy-amenable symptom was reported by 75% of women during pregnancy and postpartum in a large MS clinic based in the US.…”
Section: Alternative Therapies For Symptom-based Management For Ms An...mentioning
confidence: 99%
“…Physiotherapy and rehabilitation NICE guidelines on symptom management in MS highlight the importance of offering people with MS and mobility problems access to rehabilitation specialists and physiotherapists with expertise in MS. 11 Evidence and expert opinion have suggested that the combination of mechanical, manual and educational interventions in physiotherapy programmes which are tailored to the individual's needs may be the single most effective non-pharmacological symptomatic treatment for MS. 12 Apart from mobility, physiotherapy has also been found to be beneficial in treating cognitive and mood disturbances, pareses, spasticity and fatigue. 13 At least one physiotherapy-amenable symptom was reported by 75% of women during pregnancy and postpartum in a large MS clinic based in the US.…”
Section: Alternative Therapies For Symptom-based Management For Ms An...mentioning
confidence: 99%
“…Relevant critical events or severe deteriorations of mental or physical health have hardly ever been reported to occur in physical exercise programs for multiple sclerosis and relapses do not occur more frequently in MS patients on exercise programs. An instructive review on practical aspects of exercise training in MS is given by Learmout and Motl ( 125 ).…”
Section: Current Concepts Of Motor Fatigue In Ms: Definitions Assessm...mentioning
confidence: 99%
“…In the past decade there has been an acceleration of research in this area and there is evidence that supervised and individualized exercise programs or home-based exercise training can improve physical fitness, functional capacity, fatigue and quality of life (Sá, 2014, Halabchi et al, 2017, Ghahfarrokhi et al, 2021, Even for PwMS with severe functional impairment, exercise could be considered, in some circumstances, as an alternative valid approach to drug intervention (Edwards et al, 2017). Moreover, exercise can decrease neural apoptosis and neurodegeneration, and may be effective at stimulating neuroplasticity, speculating a disease modifying effect (Learmonth et al, 2021). There is the need however to move forward, with all stakeholders, in advancing standardized and shared outcome measures (Dalgas et al, 2021).…”
Section: Q 3 Does Multidisciplinary Care By Teams Of Different Social...mentioning
confidence: 99%